GE_GERICHTE P/13326/2018 vom 7. März 2019 - GE Cour de justice (2019)
CLASSEMENT DE LA PROCÉDURE ; FRAIS DE LA PROCÉDURE ; MOEURS ; EXCRÉMENT ; EXHIBITIONNISME | CPP.319; CP.194; CPP.426.al2; LPG.11.letc; LPG.11.lete; CPP.135